Role Of Tc99m-Besilesomab Scan With The Added Benefit Of Single Photon Emission Computed Tomography/ Computed Tomography (Spect/Ct) In Localising Infection - Mohamed Aslum Khan, Farahnaz (2017)
Imbasan Tc99m-besilesomab dengan manfaat tambahan Single Photon Emission Computed Tomography/ Computed Tomography (SPECT/CT) untuk mengenal pasti fokus lokasi infeksi dalam tubuh pesakit